SISTEM PEMANTAUAN PENGENDALIAN SUHU UDARA DAN KELEMBABAN TANAH PADA LAHAN PERTANIAN BERBASIS SCADA - Zuhud Islam Shofari; Dodi Budiman Margana; Didin Saefudin (Prosiding Industrial Research Workshop and National Seminar, 2019)
Soil moisture and air temperature are very influential factors in agricultural activities. Natural factors that are constantly changing cause moisturein the soil and temperature to become unstable. The purpose of the project that will be made is to monitor and control so that the conditions of soil moisture and temperature become stable at a certain point. The monitoring and control system on this project uses a SCADA system (Supervisory Control And Data Acquisition) and an on-off control system. In this project several sensors and actuators are used to monitor and control the plant, including soil moisture sensors, temperature sensors, solenoid valves, water pump motors, heaters and fan. The sensor will send a signal to the RTU (Remote Terminal Unit) which then the signal will be displayed on the HMI (Human Machine Interface). The test results of this project are when the temperature is above 31 ° C, the fan will be active to reduce the air temperature. If the temperature is below 25 ° C, the heater will be active. When the value of soil moisture is below 20%, the pump will be active to water the soil. By making this tool, it is expected that the conditions of soil moisture and air temperature on agricultural land can be monitored easily.Kelembaban tanah dan suhu udara merupakan faktor yang sangat berpengaruh dalam kegiatan pertanian. Faktor alam yang selalu berubah-ubah menyebabkan kelembaban pada tanah dan suhu menjadi tidak stabil. Tujuan dari alat yang akan dibuat ini adalah untuk memonitor dan melakukan pengendalian agar kondisi kelembaban tanah dan suhu menjadi stabil pada titik tertentu. Sistem monitoring dan pengendalian pada alat ini menggunakan sistem berbasis SCADA (Supervisory Control And Data Acquisition) dan sistem kendali on-off. Dalam alat ini digunakan beberapa sensor dan aktuator untuk memonitor dan mengendalikan plant, diantaranya adalah sensor kelembaban tanah, sensor suhu, solenoid valve, motor pompa air, heater dan kipas. Sensor akan mengirim sinyal ke RTU (Remote Terminal Unit) yang kemudian sinyal tersebut akan ditampilkan pada HMI (Human Machine Interface) . Hasil uji alat ini adalah ketika nilai suhu di atas 31°C maka kipas akan aktif untuk menurunkan suhu udara. Jika suhu dibawah 25°C maka heater akan aktif. Ketika nilai kelembaban tanah dibawah 20% maka pompa akan aktif untuk menyiram tanah. Dengan dibuatnya alat ini diharapkan kondisi dari kelembaban tanah dan suhu udara pada lahan pertanian dapat dipantau dengan mudah.